2018
DOI: 10.1021/jacs.7b10979
|View full text |Cite
|
Sign up to set email alerts
|

Rate-Limiting O–O Bond Formation Pathways for Water Oxidation on Hematite Photoanode

Abstract: Photoelectrochemical (PEC) water oxidation has attracted heightened interest in solar fuel production. It is well accepted that water oxidation on hematite is mediated by surface trapped holes, characterized to be the high valent -Fe═O species. However, the mechanism of the subsequent rate-limiting O-O bond formation step is still a missing piece. Herein we investigate the reaction order of interfacial hole transfer by rate law analysis based on electrochemical impedance spectroscopy (EIS) measurement and prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
181
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(188 citation statements)
references
References 42 publications
7
181
0
Order By: Relevance
“…The greater resistance to charge transfer and lower electrochemically active surface area in low‐doped domains would produce lower feedback current. This has indeed been shown with SECM, where lower boron content leads to reduced electron transfer kinetics . Furthermore, lower doping and sp 2 content would provide fewer viable binding sites for surface intermediates, leading to lower effective surface charge and greater product desorption .…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…The greater resistance to charge transfer and lower electrochemically active surface area in low‐doped domains would produce lower feedback current. This has indeed been shown with SECM, where lower boron content leads to reduced electron transfer kinetics . Furthermore, lower doping and sp 2 content would provide fewer viable binding sites for surface intermediates, leading to lower effective surface charge and greater product desorption .…”
Section: Resultsmentioning
confidence: 71%
“…This has indeed been shown with SECM, where lower boron content leads to reduced electron transfer kinetics. [16] Furthermore, lower doping and sp 2 content would provide fewer viable binding sites for surface intermediates, leading to lower effective surface charge and greater product desorption. [4] Recent work with SECCM has shown that surface termination, in addition to doping levels, greatly influences water splitting characteristics, [14] both of which may also play a factor here.…”
Section: Secm Imaging Of Heterogeneous Reactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…[36] At the same time,the first-and third-order dependence of hole formation reported by Durrant, [7] and the first-and second-order kinetics and operando observations of electrochemical water oxidation by Chen and Song, [6] support O À Oformation both at as ingle Fe atom, and at larger hole densities and/or highly basic pH values via coupling between adjacent surfacetrapped holes.F or solutions of 1 at pH 8, OÀOf ormation is more likely to occur at asingle Fe atom, giving the iron(III)- Computational results argue that the distances between adjacent Fe atoms at the hematite surface are too large to give stable peroxidebridged di-iron intermediates,Fe III ÀOOÀFe III .…”
Section: Zuschriftenmentioning
confidence: 80%
“…[2] Ag ood example is visible-light-driven water oxidation with hematite (a-Fe 2 O 3 ). Recent investigations with hematite photoanodes have quantified rates of carrier recombination, [3] identified intermediates such as Fe IV = O, [4] determined orders of reaction from one to three as afunction of the "hole" density [5] and pH value, [6] and noted the ratelimiting formation of OÀOb onds. [6,7] Forv isible-light-driven water oxidation with colloidal a-Fe 2 O 3 , [8] however,a lthough ashort hole-diffusion length of 2-4 nm [9] has been identified as the basis for increased activity at smaller particle size,very little mechanistic information is available.…”
mentioning
confidence: 99%